Biomineralization mechanism of U(VI) induced by Bacillus cereus 12-2: The role of functional groups and enzymes. (September 2018) - Zhang, Jian; Song, Han; Chen, Zhi; Liu, Shasha; Wei, Yali; Huang, Jingyi; Guo, Chuling; Dang, Zhi; Lin, Zhang
Abstract: Current studies reveal that the biomineralization of U(VI) by anaerobes normally produces nano-sized U(IV) minerals that can easily re-migrate/re-oxidize, while the biomineralization of U(VI) by aerobes has been constrained because the general mechanism has not yet been fully characterized. The biomineralization of U(VI) by Bacillus cereus 12-2 was investigated in this work. The maximum biosorption capability of intact cells was 448.68 mg U/g biomass (dry weight) at pH 5, while a decrease over 60% was induced when phosphate, amino, and especially carboxyl groups were shielded. X-ray diffraction, electron microscopy, and tracing the concentration of soluble intracellular U(VI) demonstrated that extracellular amorphous uranium particles can directly enter cells as solid, and about 10 nm-sized (NH4 )(UO2 )PO4 ·3H2 O was formed subsequently. It was also revealed that the biosorption capability was not affected by a high uranium concentration, while biomineralization was inhibited, suggesting that a high concentration of heavy metals may inhibit the enzyme activity involved in biomineralization. Besides, U(VI) could trigger the overexpression of proteins with a molecular weight of 22 kD, including various phosphatases, kinases, and other enzymes that are related to metabolism and stimulus response, which may contribute to the intracellular transformation of U(VI) compounds from amorphous to crystalline phase. Taken together, the immobilization of U(VI) by B. cereus 12-2 contains two major steps: (1) fast immobilization of U(VI) on the cell surface as amorphous compounds, in which the carboxyl groups served as the predominant coordination functional groups and (2) transport of amorphous particles to cells directly and enzyme-related formation of uramphite. Graphical abstract: The possible mechanism of uranium biomineralization by Bacillus cereus 12-2 (100 mg/L U(VI), pH = 5). Image 1 Highlights: The key functional groups related to uranium adsorption were confirmed. Extracellular amorphous uranium particles can directly enter cells as solid. Amorphous uranium particles can be transformed into nano-uramphite inside cells. Phosphatase and other enzymes are important in U(VI) phase transformation.